ANALISIS KESIAPAN GURU DALAM MERANCANG PEMBELAJARAN MEN-DALAM MELALUI PEMANFAATAN LINGKUNGAN SEKITAR SEBAGAI MEDIA KONKRET PADA MATA PELAJARAN IPA DI SEKOLAH DASAR - Ismi Luthfya Balqis; Anggia Tri Agustina; Ayatullah Muhammadin Al Fath; Erwin Efendi Hutagalung (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze teachers’ readiness in designing deep learning through the utilization of the surrounding environment as a concrete medium in science subjects at the elementary school level. A qualitative approach with a descriptive method was employed. The research subjects consisted of fourth-grade elementary school teachers. Data were collected through observation, interviews, and documentation. The findings indicate that some teachers have a basic understanding of deep learning concepts; however, they have not optimally integrated the surrounding environment as a concrete medium in lesson planning. Several challenges were identified, including limited time, lack of training, and insufficient references for contextual learning. Nevertheless, the use of the surrounding environment has proven to enhance student engagement and understanding in a more meaningful way. Therefore, efforts are needed to improve teachers’ competencies through training and mentoring programs to support the development of innovative, contextual, and experience-based learning designs.